SOCIAL SUPPORT AND ACADEMIC RESILIENCE IN ETHNIC MINAHASA OVERSEAS STUDENTS - Salim, Jovanka Tirsa Florensia; Sarajar, Dewita Karema (Counsenesia Indonesian Journal Of Guidance and Counseling, 2024)
This study aims to identify the relationship between social support and academic resilience. The research method used is quantitative method with correlational design. This study involved 77 overseas students of Satya Wacana Christian University who came from Minahasa ethnicity using saturated sampling technique. Measurements used The Academic Resilience Scale (ARS-30) (? = 0.744) and Multidimensional Scale of Perceived Social Support (MSPSS) (? = 0.789). The data analysis method used Karl Pearson's Product moment correlation test. The results showed there was a significant positive relationship between social support and academic resilience (r = 0.562, p = 0.000). r = 0.562 with a significance level of 0.000 (p < 0.05). This means that the higher the social support received by overseas students, the stronger their academic resilience. The recommendations of this study are addressed to related institutions to design psychological intervention programs and special support for overseas students, as well as to the overseas students themselves to actively seek sources of social support and develop an optimistic attitude.